2020
DOI: 10.4314/mmj.v32i3.8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and heavy metal contamination in selected commonly sold herbal medicine in Blantyre, Malawi

Abstract: BackgroundThere has been an increase in use of herbal medicine worldwide. It is either used as a stand-alone or complementary therapy to conventional medicine due to past good experience, poverty and family traditions. In Malawi, there are no regulations governing the supply, acquisition, marketing and quality enforcement of herbal medicine. This compromises its safety thereby exposing consumers to avoidable bacteria and heavy metals leading to various adverse health effects. MethodsCross-sectional laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…and Enterobacter spp., in addition to different species of Staphylococci. Comparable results were found in a recent study from Malawi (9). It has been found that microbial load in herbal products is in uenced by the climate, the antimicrobial properties of the plant, the plant surface and the distance of the plant from the soil (10).…”
Section: Discussionmentioning
confidence: 58%
“…and Enterobacter spp., in addition to different species of Staphylococci. Comparable results were found in a recent study from Malawi (9). It has been found that microbial load in herbal products is in uenced by the climate, the antimicrobial properties of the plant, the plant surface and the distance of the plant from the soil (10).…”
Section: Discussionmentioning
confidence: 58%
“…Due to the COVID-19 crisis, there is an uncontrolled release of herbal formulations and supplements as immunity boosters and antiviral drugs in the market without proper assessment of the effectiveness and microbial quality of these products. The microbial contamination of several herbal raw materials and medicines was reported in the literature [40] [41]. The consumption of such contaminated drugs with pathogenic bacteria and fungi leads to other health complications.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of iron and zinc in bean powder was done according to a method described by Kalumbi et al. (2020) with minor modifications.…”
Section: Methodsmentioning
confidence: 99%
“…Determination of iron and zinc in bean powder was done according to a method described by Kalumbi et al (2020) with minor modifications. Sample preparation for iron and zinc involved accurately weighing and mixing powdered bean samples in a clean silica crucible in preparation for wet oxidation digestion using elemental free HNO 3 -HClO 4 di-acid mixture in order to release iron and zinc.…”
Section: Crude Fat Determinationmentioning
confidence: 99%